2004
DOI: 10.1007/s10597-004-6128-2
|View full text |Cite
|
Sign up to set email alerts
|

NPACT: Enhancing Programs of Assertive Community Treatment for the Seriously Mentally Ill

Abstract: Enhancements for PACT using advanced practice nurses and consumer peer providers have the potential to address both health and mental health problems for the seriously mentally ill.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
30
0

Year Published

2005
2005
2017
2017

Publication Types

Select...
7
1

Relationship

3
5

Authors

Journals

citations
Cited by 39 publications
(32 citation statements)
references
References 22 publications
2
30
0
Order By: Relevance
“…Integrating primary care services into existing mental health programs such as ACT have shown the ability to improve mental health outcomes (Kane & Blank, 2004) and have the potential to impact medical outcomes as well. Gelberg et al (2000) found that efforts to promote health service utilization were enhanced when needs such as housing, mental health treatment, and substance abuse issues were addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Integrating primary care services into existing mental health programs such as ACT have shown the ability to improve mental health outcomes (Kane & Blank, 2004) and have the potential to impact medical outcomes as well. Gelberg et al (2000) found that efforts to promote health service utilization were enhanced when needs such as housing, mental health treatment, and substance abuse issues were addressed.…”
Section: Discussionmentioning
confidence: 99%
“…Nine studies measured clients' satisfaction with consumer-led services compared to usual mental health services. Six of these studies reported clients to have greater satisfaction with the consumer-led intervention (Burti et al 2005;Davidson et al 2004;Dumont and Jones 2002;Felton et al 1995;Greenfield et al 2008;Kane and Blank 2004), while two found no differences (Craig et al 2004;O'Donnell et al 1999). One study (Solomon and Draine 1995b) reported lower satisfaction with services in the consumer-led intervention.…”
Section: Satisfaction With Servicesmentioning
confidence: 99%
“…Twelve studies measured a variety of outcomes relating to client recovery (Burti et al 2005;Castelein et al 2008;Chinman et al 2000;Craig et al 2004;Davidson et al 2004;Felton et al 1995;Greenfield et al 2008;Kane and Blank 2004;Klein et al 1998;Nelson et al 2006b;O'Donnell et al 1999;Ochocka et al 2006). The majority of results showed either no differences, or greater recovery for those in the consumer-led interventions compared to traditional services, across all three categories of emotional, social or symptomatic recovery.…”
Section: Clients' Recovery-emotional Social Symptomatic and Practicmentioning
confidence: 99%
“…Although there is a wide literature on how ACT works in rural (Meyer and Morrissey 2007;McDonel et al 1997;Becker et al 1999;Chandler et al 1996;Drake et al 1993;Dush et al 2001;Kane and Blank 2004;Santos et al 1993;Gold et al 2006) and urban areas (Lehman et al 1997;Dixon et al 1993;Cuddeback et al 2008Cuddeback et al , 2006Essock et al 2006;Ceilley et al 2006), there has been little research to date comparing rural and urban ACT teams to determine how they vary within this context. One study compared urban and rural ACT case managers' attitudes about critical ingredients of ACT and did not find significant differences (McGrew et al 2003).…”
Section: Introductionmentioning
confidence: 99%